Automatické zjištování rozměrových změn betonových směsí při tuhnutí - Hortvík, Martin (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2017)
Tato diplomová práce se zabývá návrhem a realizací desktopové aplikace určené ke zjišťování rozměrových změn betonových směsí při tuhnutí. Součástí práce je implementace serverového portálu pro vyhodnocování získaných dat v reálném čase. Úvodní část práce se věnuje analýze úlohy a původního řešení, dále pak vymezením specifikací nové aplikace při nasazení v reálném provozu. V další části práce jsou popsány současné softwarové technologie používané při vývoji desktopových a serverových aplikací. Návrh a samotná implementace obou částí řešení tvoří podstatnou část práce. V poslední části je prezentováno ověření funkčnosti aplikace nasazené v reálném provozu.

This diploma thesis deals with the design and implementation of a desktop application designed to determine the dimensional changes of concrete mixtures during solidification. The work includes implementation of the server portal for real-time data evaluation. The introductory part deals with the analysis of the measurement task and the original solution, as well as the specification of the new application and its deployment in real operation. The next part of the thesis describes current software technologies used in the development of desktop and server applications. The design and implementation of both parts of the solution is a major part of the work. In the last part, the real-time functionality test of the application is presented.
Automatic determination of dimensional changes of concrete mixtures during solidification
Keywords: Web API; MSSQL; Entity Framework; software; C#; MVC; WPF; XAML; desktopová aplikace; AJAX; http klient; webová služba; digitální mikroskop; zpracování obrazu; Web API; MSSQL; Entity Framework; software; C#; MVC; WPF; XAML; desktop application; AJAX; http client; web service; digital microskope; image processing